2009
DOI: 10.1002/stem.259
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Cells Appearing in Pancreatic Tissue Culture Are Bone Marrow-Derived Stem Cells With the Capacity to Improve Transplanted Islet Function  

Abstract: Adherent fibroblast-like cells have been reported to appear in cultures of human endocrine or exocrine pancreatic tissue during attempts to differentiate human b cells from pancreatic precursors. A thorough characterization of these mesenchymal cells has not yet been completed, and there are no conclusive data about their origin. We demonstrated that the human mesenchymal cells outgrowing from cultured human pancreatic endocrine or exocrine tissue are pancreatic mesenchymal stem cells (pMSC) that propagate fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…In current practice, MSCs (usually obtained from adult bone marrow, adipose tissue, or neonatal umbilical cord) are among the most widely used types of adult stem cells in animal studies and human clinical trials (121, 122) for reasons that include easy isolation and expansion in culture, their comparatively infrequent abnormal differentiation or neoplastic transformation (123), their natural tropism to injured tissues (124) or cancer (123), and their potent immunomodulatory properties (122, 125, 126). For these reasons, MSC EVs are also among the most widely studied stem cell EVs and are reported to help heal a variety of stressed parenchymal tissues (113, 122), as discussed briefly below.…”
Section: Stem Cell Evs As Therapeutics: a New Paradigm For Cell-free mentioning
confidence: 99%
“…In current practice, MSCs (usually obtained from adult bone marrow, adipose tissue, or neonatal umbilical cord) are among the most widely used types of adult stem cells in animal studies and human clinical trials (121, 122) for reasons that include easy isolation and expansion in culture, their comparatively infrequent abnormal differentiation or neoplastic transformation (123), their natural tropism to injured tissues (124) or cancer (123), and their potent immunomodulatory properties (122, 125, 126). For these reasons, MSC EVs are also among the most widely studied stem cell EVs and are reported to help heal a variety of stressed parenchymal tissues (113, 122), as discussed briefly below.…”
Section: Stem Cell Evs As Therapeutics: a New Paradigm For Cell-free mentioning
confidence: 99%
“…The presence of these cells inside freshly isolated human islets was confirmed by confocal microscopy [95]. An independent study validated the presence of pancreatic MSC in the periacinar, perivascular, and periductal space of human pancreas [109]. The functional significance of the presence of these cells in the islets and the possible interplay between islet-MSC, endocrine cells, and the vascular system in human islets remain to be further clarified.…”
Section: Generation Of β-Cells From Adult Mesenchymal Stem Cells?mentioning
confidence: 97%
“…Shin et al demonstrated that the transdifferentiation capacity of human ductal cells was reduced after EMT [116]. On the other hand, Sordi et al suggested that the mesenchymal stem cell population growing out of cultured pancreatic tissue (both endocrine and exocrine fractions were tested) would be mostly originating from proliferating “pancreatic MSC” that are partly derived from the bone marrow [109]. Total bone marrow transplantations from donor GFP transgenic mice in lethally irradiated recipient mice were performed.…”
Section: Generation Of β-Cells From Adult Mesenchymal Stem Cells?mentioning
confidence: 99%
See 1 more Smart Citation
“…Ringdén et al reported that MSC transplantation plays a role in healing tissue toxicity in patients who had complications after allogeneic hematopoietic stem cell transplantation [21]. In addition, several groups have demonstrated the ability of MSCs to secrete angiogenic factors, such as vascular endothelial growth factor, hepatocyte growth factor, and interleukin-6 both in vitro [22, 23] and in vivo [24]. …”
Section: Introductionmentioning
confidence: 99%